EFEKTIFITAS ADMINISTRASI PUBLIK DALAM SISTEM PENDIDIKAN: STUDI PERBANDINGAN INDONESIA DAN JEPANG - Putri Nabila, Gadis; Aminullah (As-Sulthan Journal of Education, 2026)
Public administration effectiveness is a crucial factor in supporting the success of a country's education system. This study aims to analyze the effectiveness of public administration in the education system through a comparative study between Indonesia and Japan. The research method used is a qualitative approach using literature review techniques, including various scientific journals and relevant education policy documents. The study results indicate that public administration in education in Indonesia still faces several challenges, such as bureaucratic complexity, limited administrative capacity at the regional level, and suboptimal coordination between the central and regional governments, which impacts inequality in education quality. Meanwhile, Japan has a more structured and consistent public administration system, characterized by a clear division of authority, professionalism of its personnel, and the implementation of continuous policy evaluation. This study concludes that effective public administration contributes significantly to improving the quality and equity of education. The findings of this study are expected to serve as considerations for policymakers in efforts to improve educational administration governance in Indonesia.